Analisis Modal Manusia Pada Karyawan Perum Bulog Divre Jabar - Natari, Sari Usih; Sitio, Nurul Mardhiah (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
Perum Bulog Divre Jabar is a state-owned public company which operates in the food logistics sector. As a company that continues to carry out public duties from the government, the need for employees who have high levels of competence as human resources is highly expected, considering the company's roles and responsibilities. To realize this, a human resource concept based on human capital is needed. The aim of this research is to find out the general description of human capital and determine the influence of human capital on employees of Perum Bulog Divre Jabar either partially or simultaneously. The research method used is a descriptive and verification method using path analysis and the t-test difference test for partial testing and the F-test difference test for simultaneous testing. The data collection technique used a questionnaire distributed to 66 respondents, employees of Perum Bulog Divre Jabar. The results of this research show that human capital is in a fairly high category. The results of the path analysis show that human capital has a significant positive effect on employees of Perum Bulog Divre Jabar.